Parameters Estimation in a Mixture of TwoModified Agarwal and Kalla’s Distributions - Hussain, Shawki (Iraqi Journal of Science, 2025)
In this paper we introduced a new distribution model defined by a mixture oftwo modified Agarwal and Kalla generalized gamma distributions. Its possibleapplication in reliability is to study simultaneously both problems; the two types offailures and the displacement phenomenon. Moment and maximum likelihoodmethods were used to estimate the parameters of this distribution model, the nonlinearsystems obtained by these two methods are solved numerically using Newton-Raphson iterative technique.